(3bSWGS GdeYGOdI aj GdLHQ hGdebGHdIs
(3ChdgG (B:s
(3GdMeO ddg GdPi CMGW Hcd TF Ydeg CeG HYO aEf GdYdhe GdQjGVjI JQJbi Edi CUfGa cKjQI hCfhGY fGaYI TQjaI dcf CfaYgG Ydhe GdMSGH s
(3BNQgG (B:s
(3CYfi ef eGFg hSJI hKdGKhf CdakG hSJeGFI LRA ef Pdc GdeNQL CYfi ef eGFI hKdGKI hSJjf Cda Gda hGMO hYTQjf CdakG hKeGfeGFI hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs